Meconium peritonitis in a preterm infant: a surgical emergency - Yadav, Priyanka; Agarwal, Ankit (International Journal of Contemporary Pediatrics, 2021)
Meconium peritonitis is sterile chemical peritonitis that occurs after intestinal perforation resulting in meconium leakage and subsequent inflammatory cascade within the peritoneal cavity. The clinical presentations after birth can range from completely sealed-off peritonitis without any symptoms, to severe peritonitis requiring emergency surgical intervention. We describe a case of meconium peritonitis in a premature infant following intestinal perforation. In the immediate postnatal period, the patient was intubated and a peritoneal drain was placed. Laparotomy with bowel resection was performed the following day. The postoperative course was uneventful and the patient was discharged home in good clinical condition.